CHARACTERISTICS OF OVARIAN TUMOR CHANGES IN THE PEDIATRIC POPULATION - Konstantinović, Strahinja G; Djordjevic, Ivona; Kostic, Ana; Vacic, Nikola; Bogdanovic, Milos; Stojanovic, Dalibor (Acta medicae Medianae, 2023)
On average, a third of all adnexal masses in girls originate from the ovary. The clinical presentation is non-specific. The treatment trend is ovary-preserving surgery. The aim of the work was to present the characteristics of ovarian masses in the population of girls aged up to 18 years. This retrospective study was conducted by analyzing the medical records of female newborns and girls up to 18 years of age. In the neonatal group, aged up to 12 months, 44.4% had right-sided and 55.6% left-sided ovarian masses. Cystectomy was performed in 6 (66.7%), while ovariectomy and salpingo-oophorectomy were performed in 1 (11.1%) baby each. In the group of girls aged 1−18 years, there were 63% right-sided and 34% left-sided changes. One girl had bilateral. The largest number of girls underwent cystectomy 24 (63.2%). Of the non-neoplastic changes, there were 9 (23.6%) follicular cysts, 8 (21.1%)simple cysts, 6 (17.1%) haemorrhagic corpus luteum cysts, while of the neoplastic benign changes there were 11 (28.8%) mature teratoma, and 4 (11.4%) serous cystadenoma. The incidence of ovarian tumor changes in the population of girls up to the age of 18 is very low. Non-neoplastic changes occur much more often.